Communication Patterns in Online University Lectures: Cross-Cultural Comparison between Czechia & Indonesia - Ledvoň Natan; Nurhayati (E3S Web of Conferences, 2021)
The goal of the paper is to observe and compare the communication patterns in online university lectures occurring in the Czech and Indonesian (more specifically Javanese) environment through the lens of the ethnography of communication, based on the theory of speech acts. It aims to offer an insight in form of a case study and complement the knowledge in this field, especially considering the rapid expansion of the discourse due to the world pandemic in which information systems play a crucial role. The practical part uses direct observation of a set of classes to reveal how the same studied communicative events are practised differently. One of the key findings is the confirmation of my hypothesis that the speech events in the studied case show cultural differences and it is beneficial to study them through the lens of ethnography of communication. The focus on speech acts proved to be a crucial tool in my analysis.